Validation of the name Hedysarum damghanicum (Fabaceae, Hedysareae) from Iran - Negaresh, Kazem (Phytotaxa, 2021)
During field surveys in Damghan (Semnan Province, N Iran) I collected Hedysarum damghanicum Rechinger (1979: 237) of section Crinifera Boissier (1872: 512). In order to confirm the identity of the specimens, I examined the protologue and realized that the name Hedysarum damghanicum was not validly published, because, contrary to Art. 40.2 of ICN (Turland et al. 2018), two gatherings were designated as types: Rechinger 55373 (as “fl. Typus”) and Rechinger 56498 (as “fruct. Typus”). Therefore, the name Hedysarum damghanicum is validated here by choosing one gathering as the type.